1992
DOI: 10.1002/pro.5560010107
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylic acid‐modified polyethylene: A novel support for the covalent immobilization of polypeptides for C‐terminal sequencing

Abstract: We have developed a method for the covalent immobilization of peptides, for the purpose of C-terminal sequencing, to a novel solid support, carboxylic acid-modified polyethylene (PE-COOH) film. The peptides are attached by coupling the N-terminal amino group to the activated carboxyl groups of the film. Reagents for carboxyl group activation, including 1,3-dicyclohexylcarbodiimide (DCC), 1,l'-carbonyldiimidazole (CDI), l-ethyl-3-(3-dimethylaminopropy1)carbodiimide hydrochloride (EDC), benzotriazol-l-yl-oxy-tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The carboxyl groups of the electrografted diazonium salt were activated by incubating the functionalized electrodes in a 26 mM EDC and 35 mM sulfo-NHS solution in 100 mM MES buffer (pH 4.5) for 1 h. In order to conjugate the carboxy-fucntionalized electrode with the carboxy-modified ligands, a lysine spacer was intercalated in between, by using its two amino functionalities to form amido bonds [22][23][24][25]. The surface activated groups reacted overnight with the α-amine group of the lysine at 4°C.…”
Section: Covalent Immobilization Of Crown Ethers Via Carbodiimide Coumentioning
confidence: 99%
“…The carboxyl groups of the electrografted diazonium salt were activated by incubating the functionalized electrodes in a 26 mM EDC and 35 mM sulfo-NHS solution in 100 mM MES buffer (pH 4.5) for 1 h. In order to conjugate the carboxy-fucntionalized electrode with the carboxy-modified ligands, a lysine spacer was intercalated in between, by using its two amino functionalities to form amido bonds [22][23][24][25]. The surface activated groups reacted overnight with the α-amine group of the lysine at 4°C.…”
Section: Covalent Immobilization Of Crown Ethers Via Carbodiimide Coumentioning
confidence: 99%
“…It was found that treatment of the covalently coupled peptide with DPP-ITC in the presence of a molar excess of pyridine at 50 "C for 40 min, conditions simi-lar to those employed in the solution phase, formed peptidylthiohydantoin. Cleavage of the derivatized C-terminal amino acid was accomplished with dilute aqueous triethylamine as described above (Bailey & Shively, 1990;Shenoy et al, 1992). The presence of thiohydantoin leucine was assessed by comparison of retention time with standard thiohydantoin leucine on reverse-phase HPLC.…”
Section: Application Of the Dpp-itc Chemistry To Leucine Enkephalin Cmentioning
confidence: 99%
“…Immobilization of Rubisco was carried out on nylon membranes using 1,3-dicyclohexylcarbodiimide (DCC) as described for other enzymatic proteins in previous reports (Agarwal and Bhattacharya, 1999;Shenoy et al, 1992). Strips sized 1 × 5 × 0.05 cm with a marked and dented circular area of 0.8-cm diameter were used to immobilize the Rubisco.…”
Section: Immobilization Using the DCC Methodsmentioning
confidence: 99%
“…Twenty units of Rubisco in a final reaction volume of 50 L was applied onto the membrane in the localized (dented) circular area. Immobilization was initiated by the addition of 20 L (5 mM) of 1,3dicyclohexylcarbodiimide in the reaction mixture as described elsewhere (Shenoy et al, 1992). Each nylon membrane was soaked with 40 L of 1 g/L RuBP for 10-15 minutes (before washing with buffer).…”
Section: Immobilization Using the DCC Methodsmentioning
confidence: 99%